Photocuring composite material as well as preparation method and application thereof

The light was solved by using organic polymers of thiol-triazine triazine monomer and alkynyl-triazine triazine monomer in dental restoration materials and silica-encapsulated zirconia and hydroxyapatite nanoparticles The problem of insufficient adhesion and mechanical properties of cured composite resin in dental restoration has achieved better performance of dental restoration materials.

CN119385843APending Publication Date: 2025-02-07HEFEI ZITAI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506319.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing photocuring composite resins have problems such as poor adhesion, poor bonding of inorganic fillers and organic polymers, and poor mechanical properties and wear resistance in dental restoration.

Method used

Using organic polymers including thiol-triazine triazine monomer and alkynyl-triazine triazine monomer, combined with silica-encapsulated zirconia and hydroxyapatite nanoparticles as inorganic fillers, through photocuring technology Prepare photocured composite materials.

Benefits of technology

The mechanical strength, wear resistance and adhesion of photocured composite materials is significantly improved, and the lack of performance of conventional composite resins in teeth restoration is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119385843A_ABST
    Figure CN119385843A_ABST
Patent Text Reader

Abstract

The invention provides a photocuring composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The thiol-triazinetrione monomer and the alkynyl-triazinetrione monomer are used as monomers of the organic polymer, the alkynyl and thiol in the triazinetrione monomer are crosslinked to synthesize a new photocuring polymer, and the crosslinking density of the organic polymer can be effectively controlled, so that the mechanical property of the photocuring composite material is improved; the adhesive has excellent adhesion and mechanical properties; according to the invention, zirconium oxide and hydroxyapatite nanoparticles wrapped by silicon dioxide are utilized, and zirconium oxide and silicon dioxide have relatively good wear resistance, so that the wear resistance of the photocuring composite material can be improved; hydroxyapatite is a component of bones and can promote bone formation, improve the compatibility of the photocuring composite material and teeth and reduce cytotoxicity. Therefore, the photocuring composite material provided by the invention can be used as a photocuring composite material for dental restoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a light-cured composite material and a preparation method and application thereof. Background Art

[0002] Teeth are an indispensable chewing organ of the human body. With the increase of age and the change of living habits, the incidence of oral diseases is getting higher and higher. When teeth are damaged and defective due to diseases such as caries, it will not only damage the beauty of the teeth, but also seriously affect the normal function of the teeth. Therefore, when teeth are defective, some treatment measures need to be taken to repair the teeth. In clinical practice, doctors often choose different restorative materials to fill the cavity according to the location of the cavity of the affected tooth, the size of the bite force, the patient's health condition, and the aesthetic requirements.

[0003] At present, commonly used restorative materials include amalgam and light-cured composite resins. Light-cured composite resin is a new type of restorative material developed on the basis of acrylates. It is currently the most widely used dental restoration material in clinical practice. It is mainly composed of resin matrix and inorganic fillers. The main components of the resin matrix can be divided into two categories, one is bisphenol A-methacrylate glycidyl, and the other is methyl methacrylate. The inorganic fillers of the composite resin are mainly glass powder, silica, aluminosilicate and borate, and their content is 70% to 80% of the resin mass. Adding inorganic fillers to the resin can increase the compressive strength and hardness of the resin and reduce the expansion coefficient and volume shrinkage of the copolymer.

[0004] However, current photocurable composite resins still have the following problems: (1) poor adhesion of composite resins; (2) poor bonding between inorganic fillers and organic polymers; and (3) poor mechanical properties and wear resistance of composite resins.

[0005] Therefore, there is an urgent need to develop a light-cured composite material for tooth restoration with strong mechanical properties, wear resistance and adhesion. Summary of the invention

[0006] The purpose of the present invention is to provide a photocurable composite material and a preparation method and application thereof. The photocurable composite material provided by the present invention has excellent mechanical properties, wear resistance and adhesion after photocuring and can be used for tooth restoration.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a photocurable composite material, which comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the photocurable composite material comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the monomer of the organic polymer comprises a thiol-triazinetrione monomer and an alkynyl-triazinetrione monomer; the inorganic filler is a silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticle; the mass of the organic polymer accounts for 12-50% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 50-88% of the mass of the photocurable composite material.

[0009] Preferably, the thiol-triazinetrione monomer comprises 1,3,5-tributanethiol-triazinetrione and / or 1,3,5-tripropanethiol-triazinetrione.

[0010] Preferably, the alkynyl-triazinetrione monomer comprises 1,3,5-tripropargyl-triazinetrione and / or 1,3,5-triynylbutyl-triazinetrione.

[0011] Preferably, the mass ratio of the thiol-triazinetrione monomer to the alkynyl-triazinetrione monomer is (1-3):(1-3).

[0012] Preferably, the particle size of the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles is 200-300 nm.

[0013] Preferably, the particle size of zirconium oxide in the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles is 40 to 80 nm.

[0014] Preferably, the particle size of hydroxyapatite in the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles is 20-40 nm.

[0015] Preferably, the mass ratio of the zirconium oxide to the hydroxyapatite is 3:1-2.

[0016] The present invention also provides a method for preparing the light-curable composite material described in the above technical solution, comprising the following steps:

[0017] (1) mixing zirconium oxide, hydroxyapatite, ethanol, a silicon source and ammonia water, and performing a hydrolysis-polycondensation reaction to obtain a sol;

[0018] (2) mixing the sol obtained in step (1) with 3-thiolpropyltriethoxysilane to carry out a silane hydrolysis reaction to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0019] (3) dissolving the monomer of the organic polymer and the photoinitiator in a solvent, and then performing a light-shielding polymerization reaction to obtain an organic polymer;

[0020] (4) Mixing the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) with the organic polymer obtained in step (3) to obtain a light-curable composite material.

[0021] The present invention also provides the use of the photocurable composite material described in the above technical solution or the photocurable composite material prepared by the preparation method described in the above technical solution as a photocurable composite material for dental restoration.

[0022] The present invention provides a photocurable composite material, which comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the photocurable composite material comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the monomer of the organic polymer comprises a thiol-triazinetrione monomer and an alkynyl-triazinetrione monomer; the inorganic filler is a silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticle; the mass of the organic polymer accounts for 12-50% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 50-88% of the mass of the photocurable composite material. The present invention uses thiol-triazinetrione monomer and alkynyl-triazinetrione monomer as monomers of organic polymers, and synthesizes a new photocurable polymer by crosslinking the alkynyl group and the thiol group in the triazinetrione monomer, which can effectively control the crosslinking density of the organic polymer, thereby improving the mechanical properties of the photocurable composite material, so that it has excellent adhesion and mechanical properties; the present invention uses zirconium oxide and hydroxyapatite nanoparticles wrapped with silicon dioxide, zirconium oxide and silicon dioxide have good wear resistance, and can improve the wear resistance of the photocurable composite material; hydroxyapatite is a component of bones, which can promote bone formation, improve the compatibility of the photocurable composite material with teeth, and reduce cytotoxicity. The results of the embodiment show that the photocurable composite material provided by the present invention has excellent mechanical strength and wear resistance, and also has excellent adhesion, which solves the problems of poor adhesion of conventional composite resins, poor binding of inorganic fillers with organic polymers, and poor mechanical properties and wear resistance of composite resins. The present invention grafts 3-thiolpropyltriethoxysilane onto silicon spheres through a hydrolysis reaction, and the thiol is combined with a triazinetrione monomer (alkyne group) under the action of a photoinitiator, thereby solving the problem of poor combination of inorganic fillers and organic polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are the cytotoxicity test results of the composite material samples after curing of the light-curable composite materials prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0024] The present invention provides a photocurable composite material, which comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the photocurable composite material comprises an organic polymer and an inorganic filler dispersed in the organic polymer; the monomer of the organic polymer comprises a thiol-triazinetrione monomer and an alkynyl-triazinetrione monomer; the inorganic filler is a silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticle; the mass of the organic polymer accounts for 12-50% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 50-88% of the mass of the photocurable composite material.

[0025] The photocurable composite material provided by the invention comprises an organic polymer.

[0026] In the present invention, the monomers of the organic polymer include thiol-triazinetrione monomers and alkynyl-triazinetrione monomers. The present invention utilizes thiol-triazinetrione monomers and alkynyl-triazinetrione monomers as monomers of the organic polymer, and can utilize the alkynyl group in the organic polymer monomer to crosslink and synthesize a photocurable polymer, and utilizes the properties and positions of the functional groups to effectively change the crosslinking density, thereby improving the adhesion and mechanical properties of the photocurable material.

[0027] In the present invention, the thiol-triazinetrione monomer preferably includes 1,3,5-tributanethiol-triazinetrione and / or 1,3,5-tripropylthiol-triazinetrione, and more preferably 1,3,5-tributanethiol-triazinetrione or 1,3,5-tripropylthiol-triazinetrione. The present invention adopts the above-mentioned thiol-triazinetrione monomer, which can provide a thiol group and is more conducive to improving the adhesion and mechanical properties of the photocurable composite material.

[0028] In the present invention, the alkynyl-triazinetrione monomer preferably includes 1,3,5-tripropargyl-triazinetrione and / or 1,3,5-triynylbutyl-triazinetrione, and more preferably 1,3,5-tripropargyl-triazinetrione or 1,3,5-triynylbutyl-triazinetrione. The present invention uses the above-mentioned alkynyl-triazinetrione monomer to provide an alkynyl group, so that the alkynyl group reacts with the thiol group, thereby improving the adhesion and mechanical properties of the photocurable composite material.

[0029] In the present invention, the mass ratio of the thiol-triazinetrione monomer to the alkynyl-triazinetrione monomer is preferably (1-3): (1-3), more preferably 2: 1. The present invention controls the amount of the two monomers within the above range to allow the two monomers to react fully.

[0030] In the present invention, the mass of the organic polymer preferably accounts for 12-50% of the mass of the photocurable composite material, more preferably 20-40%, and more preferably 30-40%. The present invention controls the amount of the organic polymer within the above range, which is more conducive to fully combining the organic polymer with the inorganic filler to form a composite material with good adhesion and mechanical properties.

[0031] The photocurable composite material provided by the present invention comprises inorganic fillers dispersed in the organic polymer.

[0032] In the present invention, the inorganic filler is silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles. The present invention uses silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles as inorganic fillers. Silicon dioxide and zirconium oxide can improve the wear resistance of the photocurable composite material; hydroxyapatite can improve the compatibility of the photocurable composite material with teeth and reduce cytotoxicity.

[0033] In the present invention, the particle size of the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles is preferably 200-300 nm, more preferably 200-250 nm. The present invention controls the particle size of the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles within the above range, which has a nanoscale, is more conducive to exerting the nano effect and improving the wear resistance and hardness of the light-cured composite material.

[0034] In the present invention, the particle size of zirconium oxide in the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles is preferably 40 to 80 nm, more preferably 40 to 60 nm. In the present invention, the particle size of hydroxyapatite in the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles is preferably 20 to 40 nm, more preferably 20 to 30 nm. The present invention uses zirconium oxide and hydroxyapatite of the above particle sizes, which is more conducive to exerting the nano-size effect of zirconium oxide and hydroxyapatite.

[0035] In the present invention, the mass ratio of zirconium oxide to hydroxyapatite is preferably 3:1-2, more preferably 3:2. The present invention controls the mass ratio of zirconium oxide to hydroxyapatite within the above range, which can give full play to the role of zirconium oxide and hydroxyapatite in the photocurable composite material, so that the photocurable composite material maintains high mechanical properties and low cytotoxicity.

[0036] The present invention does not impose any particular limitation on the thickness of the silicon dioxide, as long as it can fully wrap the zirconium oxide and the hydroxyapatite.

[0037] In the present invention, the mass of the inorganic filler preferably accounts for 50-88% of the mass of the photocurable composite material, and more preferably 60-70%. The present invention controls the amount of the inorganic filler within the above range, so that the inorganic filler can be fully dispersed in the organic polymer and the wear resistance and hardness of the photocurable composite material can be improved.

[0038] The photocurable composite material provided by the present invention uses thiol-triazinetrione monomers and alkynyl-triazinetrione monomers as monomers of an organic polymer, and synthesizes a new photocurable polymer by crosslinking the alkynyl group in the triazinetrione monomer with the thiol group, which can effectively control the crosslinking density of the organic polymer, thereby improving the mechanical properties of the photocurable composite material, so that it has excellent adhesion and mechanical properties; the present invention uses zirconium oxide and hydroxyapatite nanoparticles wrapped with silicon dioxide, and zirconium oxide and silicon dioxide have good wear resistance, which can improve the wear resistance of the photocurable composite material; hydroxyapatite is a component of bones, which can promote bone formation, improve the compatibility of the photocurable composite material with teeth, and reduce cytotoxicity.

[0039] The present invention also provides a method for preparing the light-curable composite material described in the above technical solution, comprising the following steps:

[0040] (1) mixing zirconium oxide, hydroxyapatite, ethanol, a silicon source and ammonia water, and performing a hydrolysis-polycondensation reaction to obtain a sol;

[0041] (2) mixing the sol obtained in step (1) with 3-thiolpropyltriethoxysilane to carry out a silane hydrolysis reaction to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0042] (3) dissolving the monomer of the organic polymer and the photoinitiator in a solvent, and then performing a light-shielding polymerization reaction to obtain an organic polymer;

[0043] (4) mixing the silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) with the organic polymer obtained in step (3) to obtain a light-curable composite material

[0044] The invention mixes zirconium oxide, hydroxyapatite, ethanol, silicon source and ammonia water, and performs hydrolysis-polycondensation reaction to obtain sol.

[0045] In the present invention, the particle size of the zirconium oxide is preferably 40 to 80 nm, more preferably 40 to 60 nm.

[0046] In the present invention, the particle size of the hydroxyapatite is preferably 20 to 40 nm, more preferably 20 to 30 nm.

[0047] In the present invention, the mass ratio of the zirconium oxide to the hydroxyapatite is preferably 3:1-2, more preferably 3:2.

[0048] In the present invention, the ethanol is used as a solvent.

[0049] In the present invention, the mass ratio of the zirconium oxide and hydroxyapatite to the volume of ethanol is preferably 100-200 mg:1000 mL, more preferably 100 mg:1000 mL. The present invention controls the amount of the two within the above range, which is more conducive to fully dispersing zirconium oxide and hydroxyapatite in the obtained sol.

[0050] In the present invention, the silicon source preferably includes one or more of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate and butyl orthosilicate. The present invention uses the above silicon sources to provide silicon for preparing silicon dioxide.

[0051] In the present invention, the volume concentration of the ammonia water is preferably 10 to 28%, more preferably 20 to 28%. The addition of ammonia water in the present invention can promote the silicon source to form a sol.

[0052] In the present invention, the volume ratio of ethanol, silicon source and ammonia water is preferably 1000: (30-100): (100-200), and more preferably 1000: (30-50): (100-150). The present invention controls the volume ratio of ethanol, silicon source and ammonia water within the above range, so that each raw material can fully react to form a sol.

[0053] In an embodiment of the present invention, the method for mixing the zirconium oxide, hydroxyapatite, ethanol, silicon source and ammonia water can be: ball milling the zirconium oxide and hydroxyapatite to obtain a powder; stirring and mixing the powder with ethanol, silicon source and ammonia water. In an embodiment of the present invention, the ball milling speed can be 1000r / min, and the ball milling time can be 8h. The present invention can uniformly mix the zirconium oxide and hydroxyapatite through ball milling. The present invention has no special limitation on the stirring time, as long as the powder, ethanol, silicon source and ammonia water can form a uniform mixed system.

[0054] In the present invention, the hydrolysis-polycondensation reaction is preferably carried out at room temperature; the hydrolysis-polycondensation reaction time is preferably 5 to 10 hours, more preferably 8 hours. Under the above conditions, the present invention is more conducive to promoting the hydrolysis-polycondensation reaction to be more complete to obtain silica sol.

[0055] In the present invention, the hydrolysis-polycondensation reaction is preferably carried out under stirring. The present invention can promote mass transfer through stirring, so that the components are fully contacted, thereby promoting a more complete hydrolysis-polycondensation reaction and making the zirconium oxide and hydroxyapatite fully dispersed in the sol.

[0056] After obtaining the sol, the present invention mixes the sol with 3-thiolpropyltriethoxysilane to carry out a silane hydrolysis reaction to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles.

[0057] In the present invention, the 3-thiolpropyltriethoxysilane is used as a modifier to enrich the surface of the silicon sphere with thiol groups (thiol, -SH). The present invention grafts 3-thiol on the surface of the silicon sphere. During subsequent polymerization, the thiol on the surface of the silicon sphere can react with the alkynyl group, so that the organic component (triazinetrione) and the inorganic component (silicon sphere, zirconium oxide, hydroxyapatite) are connected together through chemical reactions, thereby improving the bonding strength between the inorganic filler and the organic component. In the present invention, the volume ratio of the silicon source to the 3-thiolpropyltriethoxysilane is preferably (30-100): (10-20), and more preferably (30-50): (10-15). The present invention controls the amount of the two within the above range, which can ensure that the surface of the silicon sphere is grafted with thiol groups without 3-thiolpropyltriethoxysilane residue.

[0058] In the present invention, the method of mixing the sol and 3-thiolpropyltriethoxysilane is preferably stirring. In an embodiment of the present invention, the stirring speed can be 1000r / min. The present invention is more conducive to more uniform mixing of the sol and 3-thiolpropyltriethoxysilane through stirring.

[0059] In the present invention, the silane hydrolysis reaction is preferably carried out at room temperature, and the time of the silane hydrolysis reaction is preferably 2 to 5 hours, more preferably 4 hours. The present invention is more conducive to promoting the full progress of the silane hydrolysis reaction under the above conditions.

[0060] In the present invention, the silane hydrolysis reaction is preferably carried out under stirring. In an embodiment of the present invention, the stirring speed may be 1000 r / min. The present invention is more conducive to mass transfer through stirring, and promotes the silane hydrolysis reaction to be more complete.

[0061] In the present invention, after the silane hydrolysis reaction, the system obtained by the silane hydrolysis reaction is preferably subjected to solid-liquid separation, washing and drying in sequence to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles. The present invention does not specifically limit the solid-liquid separation, washing and drying methods, and conventional solid-liquid separation, washing and drying operation methods can be used. In an embodiment of the present invention, the solid-liquid separation method can be centrifugal filtration; the washing reagent can be water or ethanol.

[0062] The invention dissolves the monomer of the organic polymer and the photoinitiator in a solvent, and then performs a light-shielding polymerization reaction to obtain the organic polymer.

[0063] In the present invention, the monomers of the organic polymer are the same as the monomers of the organic polymer described in the above technical solution, and will not be described in detail here.

[0064] In the present invention, the photoinitiator preferably includes BASF 819, BASF TPO or BASF 784, more preferably BASF 819. In the present invention, by adding a photoinitiator, the photocurable composite material can be further cured by light during application, so that it can be bonded to the teeth.

[0065] In the present invention, the mass ratio of the organic polymer monomer to the photoinitiator is preferably 5 to 24: 1, more preferably 16 to 18: 1. The present invention controls the usage of the two within the above range, so that the photocurable composite material can be fully crosslinked and cured under light.

[0066] In the present invention, the solvent preferably includes one or more of dichloromethane, 1,2-dichloroethane and chloroform, and more preferably dichloromethane or 1,2-dichloroethane. The above solvents are more conducive to dissolving the triazinetrione monomer and the photoinitiator.

[0067] The present invention has no special limitation on the amount of the solvent, as long as it can completely dissolve the monomers of the organic polymer and the photoinitiator.

[0068] In the present invention, the light-shielding polymerization reaction is preferably carried out at room temperature, and the light-shielding polymerization reaction time is preferably 1 to 5 days, more preferably 4 days. Under the above conditions, the present invention can fully polymerize the triazinetrione monomer.

[0069] The present invention has no special limitation on the method of light-shielding. A conventional method can be used to block light from irradiating the triazinetrione monomer, the photoinitiator and the solvent mixed solution. In an embodiment of the present invention, the method of light-shielding can be wrapping the reaction container with tin foil. The present invention can prevent the triazinetrione monomer from reacting with the photoinitiator before it is fully polymerized by light-shielding.

[0070] In the present invention, after the light-shielded polymerization reaction, the solvent is preferably removed to obtain an organic polymer. The present invention has no particular limitation on the method for removing the solvent, and any conventional method for removing the solvent may be used. In an embodiment of the present invention, the method for removing the solvent may be drying.

[0071] After obtaining the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles and the organic polymer, the present invention mixes the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles with the organic polymer to obtain a light-cured composite material.

[0072] In the present invention, the mass ratio of the silica-encapsulated zirconium oxide to the hydroxyapatite nanoparticles to the organic polymer is preferably (50-88):(12-50), and more preferably (50-70):(30-50).

[0073] In the present invention, the method of mixing the silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles with the organic polymer is preferably stirring. The present invention has no particular limitation on the speed and time of the stirring, as long as the two can be mixed evenly.

[0074] The method provided by the invention is simple to operate and can synthesize a new photocurable polymer by cross-linking the alkynyl group and the thiol group in the monomer of the organic polymer, thereby improving the mechanical properties and adhesion of the photocurable material.

[0075] The present invention also provides the use of the photocurable composite material described in the above technical solution or the photocurable composite material prepared by the preparation method described in the above technical solution as a photocurable composite material for dental restoration.

[0076] In the present invention, the method of using the light-curable composite material as a light-curable composite material for dental restoration preferably comprises: filling the light-curable composite material in the part of the tooth that needs to be restored, and curing it under light.

[0077] In the present invention, the wavelength of the light source of the illumination is preferably 375 to 525 nm, more preferably 375 nm; the energy of the light source of the illumination is preferably 1500 to 2000 mW / cm 2 , more preferably 2000mW / cm 2 The present invention has no special limitation on the illumination time, as long as the light-curable composite material can be completely cured. Under the above illumination conditions, the present invention is more conducive to the photoinitiator promoting the full crosslinking and curing of the light-curable composite material.

[0078] The present invention utilizes thiol-triazinetrione monomers and alkynyl-triazinetrione monomers as monomers of organic polymers, and synthesizes new photocurable polymers by crosslinking the alkynyl and thiol groups in the triazinetrione monomers, so that the crosslinking density of the organic polymer can be effectively controlled, thereby improving the mechanical properties of the photocurable composite material, and making it have excellent adhesion and mechanical properties; the present invention utilizes zirconium oxide and hydroxyapatite nanoparticles wrapped in silicon dioxide, and zirconium oxide and silicon dioxide have good wear resistance, which can improve the wear resistance of the photocurable composite material; hydroxyapatite is a component of bones, which can promote bone formation, improve the compatibility of the photocurable composite material with teeth, and reduce cytotoxicity, so that it can be used as a photocurable composite material for dental restoration.

[0079] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0080] Example 1

[0081] A photocurable composite material, the photocurable composite material is composed of an organic polymer and an inorganic filler dispersed in the organic polymer; the monomers of the organic polymer are 1,3,5-tripropanethiol-triazinetrione monomer and 1,3,5-tripropargyl-triazinetrione monomer; the inorganic filler is silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles; the mass of the organic polymer accounts for 34.6% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 65.4% of the mass of the photocurable composite material;

[0082] The preparation method of the light-curable composite material is as follows:

[0083] (1) 20 nm zirconium oxide nanoparticles and 40 nm hydroxyapatite nanoparticles were added to a ball mill at a mass ratio of 3:2, and mixed thoroughly for 8 h. Then, 100 g of the powder was ultrasonically stirred with 1000 mL of ethanol and 30 mL of ethyl orthosilicate, and then 100 mL of 25% ammonia water was added. The mixture was stirred at room temperature for 8 h for hydrolysis-polycondensation reaction to obtain a sol;

[0084] (2) the sol obtained in step (1) was reacted with 10 mL of 3-thiolpropyltriethoxysilane for 4 h at a speed of 1000 r / min, the obtained white solid was centrifuged and filtered, washed three times with water and ethanol respectively, and dried to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0085] (3) 1.5 g of 1,3,5-tripropanethiol-triazinetrione monomer, 0.5 g of 1,3,5-tripropargyl-triazinetrione monomer, and 0.12 g of a photoinitiator (BASF 819) were added to a single-necked bottle, 4 mL of 1,2-dichloroethane was added to dissolve, the outer wall was wrapped with tin foil, mixed, and allowed to stand for 4 days to perform a light-proof polymerization reaction, and then dried to remove the solvent to obtain an organic polymer;

[0086] (4) 4.0 g of the silica-coated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) and the organic polymer obtained in step (3) are mixed evenly to obtain a photocurable composite material.

[0087] Example 2

[0088] A photocurable composite material, the photocurable composite material is composed of an organic polymer and an inorganic filler dispersed in the organic polymer; the monomers of the organic polymer are 1,3,5-tripropanethiol-triazinetrione monomer and 1,3,5-tripropargyl-triazinetrione monomer; the inorganic filler is silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles; the mass of the organic polymer accounts for 41.4% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 58.6% of the mass of the photocurable composite material;

[0089] The preparation method of the light-curable composite material is as follows:

[0090] (1) 20 nm zirconium oxide nanoparticles and 40 nm hydroxyapatite nanoparticles were added to a ball mill at a mass ratio of 3:2, and the mixture was fully mixed for 8 h to obtain a powder. Then, 100 g of the powder was ultrasonically stirred with 1000 mL of ethanol and 30 mL of ethyl orthosilicate, and then 100 mL of 25% ammonia water was added and stirred at room temperature for 8 h for hydrolysis-polycondensation reaction to obtain a sol.

[0091] (2) the sol obtained in step (1) was reacted with 10 mL of 3-thiolpropyltriethoxysilane for 4 h at a speed of 1000 r / min, the obtained white solid was centrifuged and filtered, washed three times with water and ethanol respectively, and dried to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0092] (3) 1.5 g of 1,3,5-tripropanethiol-triazinetrione monomer, 0.5 g of 1,3,5-tripropargyl-triazinetrione monomer, and 0.12 g of a photoinitiator (BASF 819) were added to a single-necked bottle, 4 mL of 1,2-dichloroethane was added to dissolve, the outer wall was wrapped with tin foil, mixed, and allowed to stand for 4 days to perform a light-proof polymerization reaction, and then dried to remove the solvent to obtain an organic polymer;

[0093] (4) The silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles 3 g obtained in step (2) and the organic polymer obtained in step (3) are uniformly mixed to obtain a photocurable composite material.

[0094] Example 3

[0095] A photocurable composite material, the photocurable composite material is composed of an organic polymer and an inorganic filler dispersed in the organic polymer; the monomers of the organic polymer are 1,3,5-tripropanethiol-triazinetrione monomer and 1,3,5-tripropargyl-triazinetrione monomer; the inorganic filler is silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles; the mass of the organic polymer accounts for 45.9% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 54.1% of the mass of the photocurable composite material;

[0096] The preparation method of the light-curable composite material is as follows:

[0097] (1) 20 nm zirconium oxide nanoparticles and 40 nm hydroxyapatite nanoparticles were added to a ball mill and mixed thoroughly for 8 h. Then, 100 g of the powder was ultrasonically stirred with 1000 mL of ethanol and 30 mL of ethyl orthosilicate. Then, 100 mL of 25% ammonia water was added and stirred at room temperature for 8 h for hydrolysis-polycondensation reaction to obtain a sol.

[0098] (2) the sol obtained in step (1) was reacted with 10 mL of 3-thiolpropyltriethoxysilane for 4 h at a speed of 1000 r / min, the obtained white solid was centrifuged and filtered, washed three times with water and ethanol respectively, and dried to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0099] (3) 1.5 g of 1,3,5-tripropanethiol-triazinetrione monomer, 0.5 g of 1,3,5-tripropargyl-triazinetrione monomer, and 0.12 g of a photoinitiator (BASF 819) were added to a single-necked bottle, 4 mL of 1,2-dichloroethane was added to dissolve, the outer wall was wrapped with tin foil, mixed, and allowed to stand for 4 days to perform a light-proof polymerization reaction, and then dried to remove the solvent to obtain an organic polymer;

[0100] (4) 2.5 g of the silica-coated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) and the organic polymer obtained in step (3) are uniformly stirred to obtain a photocurable composite material.

[0101] Comparative Example 1

[0102] A photocurable composite material, the photocurable composite material is composed of an organic polymer and an inorganic filler dispersed in the organic polymer; the monomer of the organic polymer is a 1,3,5-tripropargyl-triazinetrione monomer; the inorganic filler is a silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticle; the mass of the organic polymer accounts for 34.6% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 65.4% of the mass of the photocurable composite material;

[0103] The preparation method of the light-curable composite material is as follows:

[0104] (1) 20 nm zirconium oxide nanoparticles and 40 nm hydroxyapatite nanoparticles were added to a ball mill and mixed thoroughly for 8 h. Then, 100 g of the powder was ultrasonically stirred with 1000 mL of ethanol and 30 mL of ethyl orthosilicate. Then, 100 mL of 25% ammonia water was added and stirred at room temperature for 8 h for hydrolysis-polycondensation reaction to obtain a sol.

[0105] (2) the sol obtained in step (1) was reacted with 10 mL of 3-thiolpropyltriethoxysilane for 4 h at a speed of 1000 r / min, the obtained white solid was centrifuged and filtered, washed three times with water and ethanol respectively, and dried to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles;

[0106] (3) 2.0 g of 1,3,5-tripropargyl-triazinetrione monomer and 0.12 g of photoinitiator (BASF 819) were added to a single-necked bottle, 4 mL of 1,2-dichloroethane was added to dissolve, the outer wall was wrapped with tin foil, mixed, and allowed to stand for 4 days to perform light-protected polymerization reaction, and then dried to remove the solvent to obtain an organic polymer;

[0107] (4) 4.0 g of the silica-coated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) and the organic polymer obtained in step (3) are mixed evenly to obtain a photocurable composite material.

[0108] Comparative Example 2

[0109] A photocurable composite material, the photocurable composite material is composed of an organic polymer; the monomers of the organic polymer are 1,3,5-tripropanethiol-triazinetrione monomer and 1,3,5-tripropargyl-triazinetrione monomer;

[0110] The preparation method of the photocurable composite material is as follows: 1.5 g of 1,3,5-tripropanethiol-triazinetrione monomer, 0.5 g of 1,3,5-tripropargyl-triazinetrione monomer, and 0.12 g of a photoinitiator (BASF 819) are added into a single-necked bottle, 4 mL of 1,2-dichloroethane is added to dissolve, the outer wall is wrapped with tin foil, mixed, left to stand for 4 days to perform light-proof polymerization reaction, and then dried to remove the solvent to obtain an organic polymer, namely the photocurable composite material.

[0111] Application Example 1

[0112] A method for using a light-curing composite material as a light-curing composite material for dental restoration: the light-curing composite material prepared in Example 1 is dispersed and defoamed, poured into a mold, and irradiated with a light source having a wavelength of 375 nm and a light source energy of 2000 mW / cm 2 The composite material is cured under light source.

[0113] Application Example 2

[0114] A method for using a light-curing composite material as a light-curing composite material for dental restoration: the light-curing composite material prepared in Example 2 is dispersed and defoamed, poured into a mold, and irradiated with a light source having a wavelength of 375 nm and a light source energy of 2000 mW / cm 2 The composite material is cured under light source.

[0115] Application Example 3

[0116] A method for using a light-curing composite material as a light-curing composite material for dental restoration: the light-curing composite material prepared in Example 3 is dispersed and defoamed, poured into a mold, and irradiated with a light source having a wavelength of 375 nm and a light source energy of 2000 mW / cm 2 The composite material is cured under light source.

[0117] Comparative application example 1

[0118] A method for using a light-curing composite material as a light-curing composite material for dental restoration: the light-curing composite material prepared in comparative example 1 is dispersed and defoamed, poured into a mold, and irradiated with a light source having a wavelength of 375 nm and a light source energy of 2000 mW / cm 2 The composite material is cured under light source.

[0119] Comparative Application Example 2

[0120] A method for using a light-curing composite material as a light-curing composite material for dental restoration: the light-curing composite material prepared in comparative example 2 is dispersed and defoamed, poured into a mold, and irradiated with a light source having a wavelength of 375 nm and a light source energy of 2000 mW / cm 2 The composite material is cured under light source.

[0121] Test Case

[0122] (1) Cytotoxicity assay

[0123] Preparation of extract: The extract was prepared according to the national standard GB / T 16886.12-2005. The composite material samples cured by the light-curable composite material prepared in Examples 1 to 3 were added to the cell culture medium, and the extraction ratio was 3 cm 2 / mL, then cultured in a 37°C incubator for 24 h, and the obtained extract was refrigerated at 4°C for later use.

[0124] The extract was added to a 96-well plate, 2,000 cells were seeded per well, 10% FBS was added to each well, and the cells were cultured at 37°C in 5% CO2 for 7 days. TM The Zoom system was used to observe the effects of the extract on human embryonic lung fibroblasts (MRC-5) in real time. Figure 1 The figure shows the survival rate of MRC-5 cells cultured in the extract for 1, 3 and 5 days. Figure 1It can be seen that the relative cell survival rate of the composite materials after curing of the light-curable composite materials prepared in Examples 1 to 3 is comparable to that of the control group, indicating that the prepared samples have no cytotoxicity. This is because the present invention uses silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles, and hydroxyapatite is a component of bones, which can promote bone formation, improve the compatibility of light-curable composite materials with teeth, and reduce cytotoxicity.

[0125] (2) Mechanical properties test

[0126] The composite material samples prepared by using a universal material machine (Instron 5966) corresponding to Examples 1 to 3 and Comparative Application Examples 1 to 2 were tested in the following experiments:

[0127] Flexural strength: The composite material was cut into 25 mm × 2 mm × 2 mm test specimens and subjected to a three-point bending test, with 3 specimens in each group.

[0128] Compression strength: The compression strength of the material is tested through a compression test. The specimen is a cylinder with a particle size of 15mm and a height of 15mm, with 3 specimens in each group.

[0129] Wear resistance test: The wear resistance of the composite resin was evaluated using a sliding friction tester. After 10,000 wear cycles, the wear value was measured, with 3 samples in each group.

[0130] Adhesion test: The bond strength test was carried out using a universal tensile machine. In compression mode, a 500N load cell was used with a moving speed of 10mm / min. The test substrate was bovine tooth enamel.

[0131] The flexural strength and compressive strength test results of the composite material samples are shown in Table 1.

[0132] Table 1 Strength test results of composite material samples prepared in Application Examples 1 to 3 and Comparative Application Examples 1 to 2

[0133] Flexural strength / MPa Compression strength / MPa <![CDATA[Volume wear value / mm 3 > Adhesion test Application Example 1 520 572 73 35 Application Example 2 535 581 62 38 Application Example 3 540 588 58 41 Comparative application example 1 150 200 240 5 Comparative Application Example 2 120 180 280 7

[0134] It can be seen from Table 1 that compared with the composite material samples prepared in comparative application examples 1 to 2, the flexural strength and compressive strength of the composite material samples prepared in application examples 1 to 3 are greatly improved. This is because the present invention utilizes thiol-triazinetrione monomers and alkynyl-triazinetrione monomers as monomers of the organic polymer, and synthesizes a new photocurable polymer by crosslinking the alkynyl and thiol groups in the triazinetrione monomer, which can effectively control the crosslinking density of the organic polymer, thereby improving the mechanical properties of the photocurable composite material, so that it has excellent adhesion and mechanical properties.

[0135] (3) Polymerization volume shrinkage

[0136] The volume shrinkage rate was calculated by measuring the density of the composite resin before and after curing. At the same temperature, the density of the composite resin before and after curing was measured by the Archimedes method using a density balance, and each group of samples was weighed three times.

[0137] Table 2 Shrinkage test results of composite material samples prepared in Application Examples 1 to 3 and Comparative Application Examples 1 to 2

[0138] Shrinkage % Application Example 1 1.25 Application Example 2 1.32 Application Example 3 1.27 Comparative application example 1 1.62 Comparative Application Example 2 1.73

[0139] It can be seen from the above results that the photocurable composite material provided by the present invention has excellent mechanical strength and wear resistance, as well as excellent adhesion, which solves the problems of poor adhesion of conventional composite resins, poor bonding between inorganic fillers and organic polymers, and poor mechanical properties and wear resistance of composite resins.

[0140] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A photocurable composite material, comprising an organic polymer and an inorganic filler dispersed in the organic polymer; the monomers of the organic polymer comprise thiol-triazinetrione monomers and alkynyl-triazinetrione monomers; the inorganic filler is silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles; the mass of the organic polymer accounts for 12 to 50% of the mass of the photocurable composite material; the mass of the inorganic filler accounts for 50 to 88% of the mass of the photocurable composite material.

2. The light-curable composite material according to claim 1, characterized in that: The thiol-triazinetrione monomer includes 1,3,5-tributanethiol-triazinetrione and / or 1,3,5-tripropanethiol-triazinetrione.

3. The light-curable composite material according to claim 1 or 2, characterized in that: The alkynyl-triazinetrione monomer includes 1,3,5-tripropargyl-triazinetrione and / or 1,3,5-triynylbutyl-triazinetrione.

4. The light-curable composite material according to claim 1 or 2, characterized in that: The mass ratio of the thiol-triazinetrione monomer to the alkynyl-triazinetrione monomer is (1-3): (1-3).

5. The light-curable composite material according to claim 1, characterized in that: The particle size of the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles is 200-300 nm.

6. The light-curable composite material according to claim 1 or 5, characterized in that: The particle size of zirconium oxide in the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles is 40-80 nm.

7. The light-curable composite material according to claim 1 or 5, characterized in that: The particle size of hydroxyapatite in the silicon dioxide-wrapped zirconium oxide and hydroxyapatite nanoparticles is 20-40 nm.

8. The light-curable composite material according to claim 1 or 5, characterized in that: The mass ratio of the zirconium oxide to the hydroxyapatite is 3:1-2.

9. The method for preparing the photocurable composite material according to any one of claims 1 to 8, comprising the following steps: (1) mixing zirconium oxide, hydroxyapatite, ethanol, a silicon source and ammonia water, and performing a hydrolysis-polycondensation reaction to obtain a sol; (2) mixing the sol obtained in step (1) with 3-thiolpropyltriethoxysilane to carry out a silane hydrolysis reaction to obtain silicon dioxide-coated zirconium oxide and hydroxyapatite nanoparticles; (3) dissolving the monomer of the organic polymer and the photoinitiator in a solvent, and then performing a light-shielding polymerization reaction to obtain an organic polymer; (4) Mixing the silicon dioxide-encapsulated zirconium oxide and hydroxyapatite nanoparticles obtained in step (2) with the organic polymer obtained in step (3) to obtain a light-curable composite material.

10. Use of the photocurable composite material according to any one of claims 1 to 8 or the photocurable composite material prepared by the preparation method according to claim 9 as a photocurable composite material for dental restoration.